Muslim consumer's awareness and acceptance on halal genetically modified food labelling - Md Rapi, Nurul Razanah; Kamarulzaman, Nitty Hirawaty; Ismail, N. W. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Genetically modified (GM) foods have been produced from the development of modern biotechnology and gene combination of same or different species. GM foods have risen many concerns arisen due to religious, ethical, moral, health, environment effect, virus, and toxin. This has become an important issue among Muslim consumers in consuming halalan toyyiban food produced from GM foods. Therefore, having such labelling is an important element to provide a clear declaration or information on the ingredients of the food products to consumers particularly Muslims to make right purchasing choices and decisions. In the light of the above discussion, the objectives of the study are 1) to determine Muslim consumers’ awareness and acceptance on halal GM foods, and 2) to investigate GM foods labelling that influence Muslim consumers’ awareness and acceptance of halal GM foods. The conceptual framework of the study was based on Attitude Model of GM Food. A survey was carried out with 320 respondents using a simple random sampling technique across Klang Valley and was measured using structured questionnaires with a 5-point Likert-scale related to awareness and acceptance towards halal GM foods labelling. The data was analysed using descriptive analysis, chi-square analysis and factor analysis. Descriptive analysis showed that majority of the respondents were not aware of the existence of halal GM foods labelling. Chi-square results revealed that that there are association between age, education level and household income towards Muslim consumers’ awareness on halal GM foods labelling. Factor analysis identified health concern, religious belief and labelling have influenced Muslim consumers’ acceptance on halal GM foods. This study emphasized that labelling could help Muslim consumers to improve their awareness and acceptance on halal GM foods.